Effects of adhesive system, thermal aging and ceramic shade on the final color and bond strength of monolithic lithium disilicate ceramics - Parlar Oz, Ozge (Annals of Medical Research, 2021)
Aim: The present study aims to observe the effects of adhesive systems and thermocycling on the final color of monolithic lithium disilicate ceramics, also impacts of ceramic shade on the bond strength of resin cement.Material and Methods: Monolithic lithium disilicate ceramic discs in VITA shades A1 and A3 and also self-adhesive, self-etch and total-etch adhesive resin cement systems that were used were investigated in this study. The same color of resin cement (A2 shade) was used for cementation. Ceramic samples of 0,5 mm in thickness were obtained from the IPS e.max CAD blocs. All specimens were distributed into two main groups and six subgroups (n=10) according to the ceramic shade and adhesive system. All specimens were exposed to thermocycling (10,000 cycles). A contact spectrophotometer measured the color differences according to the CIEL*a*b* system. The color differences between before resin cementation (1), after resin cementation procedure (2) and after thermocycling (3), were evaluated. Shear bond strength test was performed after thermocycling.Results: All L values decreased after the resin cementation. The A3-VL (total etch-A3) group had statistically significantly lowest values of L* (p0.05). A3-RX (self-adhesive-A3) group had the statistically significant highest a* and b* values (p0.05). A3-RX group had the highest bond strength results, and there were no statistically significant differences between the A1-VL group (p>0.05). Conclusions: All of the adhesive systems affected the final color of ceramics. Otherwise, the thermal aging procedure did not lead to the changes in the color of the ceramic-resin specimen. Furthermore, ceramic shade affected the bond strength of resin cement after thermocycling.